The Influence of Islamic Financial Literacy, Income and Financial Behavior on Investment Decisions During The Covid-19 Pandemic - Pahlevi, Cepi; Nurlia; Musa, Ichwan; Anwar, Vebby; Norhaedah, Norhaedah; Evendi, Agustina Martha (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This study was conducted to examine Islamic Financial Literacy, Income and Financial Behavior which partly influence the investment decisions of PT. Pegadaian, Regional Office IVl Balikpapan. This type of research is quantitative with data sources from questionnaire results. The sample in this study was 100l customers of PT. Pegadaian Regional Office IVl Balikpapan uses the Slovin formula. Researchers used IBM's statistical application SPSS 26. The application is used to test instrument tests, classical assumption tests, multiple linear regression analysis and research hypothesis tests. The results of the analysis show that Islamic financial literacy, income and financial behavior have a positive and significant effect on investment decisions. Islamic Financial Behavior Variables have a dominant influence on other variables.